Delphi-AHP 방법을 이용한 저탄소수소 생산 기술 가치평가 모델 개발 - 황호석(HO SEOK WHANG); 김의식(UISIK KIM); 장영신(YOUNGSHIN JANG); 김정환(JUNGHWAN KIM); 김광준(KWANG JUN KIM) (한국수소 및 신에너지학회 논문집, 2023)
Recently, low hydrogen carbon production technology is drawing interest due to lower production costs. Although the pace of research in this field has been accelerating, there is no well-established criteria for evaluation. The most of current evaluation methods needs information related to technology. However the technology is not enough to provide effective evaluation criteria because the technology is not fully developed. In this study, we propose an integrated Delphi-analytic hierarchy process (AHP) method and low carbon hydrogen production technology evaluation model. Experts opinion is used to provide evaluation criteria for the technology. In this study, integrated Delphi-AHP method are utilized for determining factors and calculating their numerical importance based on experts opinion. Then, sensitivity analysis is performed to verify the robustness of the analysis and scenarios of potential changes. As many as 11 factors are identified by Delphi method. Then, numerical importance of the factors are calculated by AHP. Sensitivity analysis is performed. It shows that intellectual property right (IPR) is always more important than other factors. This study proposes the numerical standard for the low carbon hydrogen production technology evaluation. The proposed model can be used for technology evaluation or commercialization.